Challenging Issues in Translating Conversational Implicature from English into Arabic - Al-Shawi, Muna Ahmad; Tengku Mahadi, Tengku Sepora (Australian International Academic Centre (AIAC), 2017)
Conversational implicature is known as an additional meaning indirectly implicated by saying another thing. In this sense, the aim of this paper is to discuss the problems of translating conversational implicature from English into Arabic. the data is selected from two English literary works; Lord of the Flies and Nineteen Eighty-Four along with their Arabic translation. Two theoretical frameworks are implemented for the descriptive analysis of the selected texts, Skopos approach and Grice’s Implicature. These two theories, along with their rules, provide appropriate standards to measure the accuracy of such translations from English language into Arabic. The analyses reveal that the translators encountered problems and obstacles during the translation into Arabic for several reasons, including linguistic, social and cultural. therefore, the translators followed different approaches and techniques to achieve consistent coherent Arabic text, equivalent to that of the original. In conclusion, the study illustrates that both theories are successful and applicable at varying levels, in translating conversational implicature from English into Arabic. Nevertheless, Grice’s approach is more successful in translating the conversational imlicatures within the framework of this study. Accordingly, this study answers all the designed questions.